Mode-Specific Vibrational Autodetachment Following Excitation of Electronic Resonances by Electrons and Photons - Anstöter, Cate S; Mensa-Bonsu, Golda; Nag, Pamir; Ranković, Miloš; Kumar T P, Ragesh; Boichenko, Anton N; Bochenkova, Anastasia V; Fedor, Juraj; Verlet, Jan R R (Physical review letters, 2020)
Electronic resonances commonly decay via internal conversion to vibrationally hot anions and subsequent statistical electron emission. We observed vibrational structure in such an emission from the nitrobenzene anion, in both the 2D electron energy loss and 2D photoelectron spectroscopy of the neutral and anion, respectively. The emission peaks could be correlated with calculated nonadiabatic coupling elements for vibrational modes to the electronic continuum from a nonvalence dipole-bound state. This autodetachment mechanism via a dipole-bound state is likely to be a common feature in both electron and photoelectron spectroscopies.